Vitamin D inhibits proliferation and profibrotic marker expression in hepatic stellate cells and decreases thioacetamide-induced liver fibrosis in rats. Issue 12 (4th August 2011) - Abramovitch, Shirley; Dahan-Bachar, Liora; Sharvit, Efrat; Weisman, Yosef; Tov, Amir Ben; Brazowski, Eli; Reif, Shimon
Abstract : Background and aim: Hepatic stellate cells (HSCs) are key participants in liver fibrosis development. 1, 25(OH)2 D3, the active form of vitamin D, has antiproliferative properties and antifibrotic potential, as well as a role in extracellular matrix and matrix metalloproteinase (MMP) regulation in renal and lung fibrosis. Little is known about the role of 1, 25(OH)2 D3 in liver and its involvement in liver fibrosis. Therefore, we investigated the antiproliferative and antifibrotic effects of 1, 25(OH)2 D3 in primary cultured HSCs and in a rat model of liver fibrosis induced by thioacetamide (TAA). Methods: Primary HSCs were isolated from rats' livers and treated with 1, 25(OH)2 D3 . Proliferation was examined by bromodeoxyuridine. Vitamin D receptor (VDR) expression and several fibrotic markers were detected by western blot analysis and real-time PCR. Collagen Iα1 and MMP-9 promoter activity were measured by luciferase assay. MMP-9 enzymatic activity was investigated by zymography. VDR silencing was performed by sh-RNA. An in vivo study was performed on TAA-induced liver fibrosis model in rats treated with or without 1, 25(OH)2 D3 . The fibrotic score and collagen deposition were determined by Masson and by Sirius red staining. Results: While VDR was highly expressed in quiescent HSCs, its expression decreased up to 40% during activation. Addition of 1, 25(OH)2 D3 to activated HSCs stimulated VDR expression. 1, 25(OH)2 D3 suppressed HSC proliferation and cyclin D1 expression by ∼50% and tissue inhibitor of metalloproteinase 1 (TIMP-1) by 60% and led to a 40% downregulation of collagen Iα1 expression. Moreover, 1, 25(OH)2 D3 increased MMP-9 activity by 30%. Silencing VDR by sh-RNA demonstrated that suppression of cyclin D1 and collagen Iα1 protein expression was VDR dependent. Treatment with 1, 25(OH)2 D3 significantly reduced extracellular matrix deposition and lowered the fibrotic score in TAA-induced liver fibrosis. Conclusion: 1, 25(OH)2 D3 has antiproliferative and antifibrotic effects on liver fibrosis in in vitro and in vivo models and may be considered as having potential therapeutic value.